Estimating the Motion of Shock and Vibration System and Performance of Oscillation Limiters Based on Time and Shape of Shock Pulse of the Shock and Vibration Machine - Nazarenko, Ivan; Nesterenko Jr, Mykola; Orysenko, Oleksandr; Zygun, Alina (International Journal of Engineering and Technology, 2018)
The paper describes an analytic dependence for determining the amplitude of oscillations on a fundamental frequency with the definition of the limit on the amplitude of the super resonance harmonic. In the article the conditions are formulated and dependences for a system moving in shock and up to shock mode: time of impact, deformation of limiters, recovery factor, velocity after the end of interaction are defined.Â Â Â Â Â Â Â Â Â Â Â Â Â